Synthesis of Ag–Ho, Ag–Sm, Ag–Zn, Ag–Cu, Ag–Cs, Ag–Zr, Ag–Er, Ag–Y and Ag–Co metal organic nanoparticles for UV-Vis-NIR wide-range bio-tissue imaging. Issue 5 (31st January 2019) - Wu, Ye; Lin, Yingcheng; Xu, Jian
Abstract : Development of materials for fluorescence imaging with a wide optical range is important for clinical applications. Abstract : Development of materials for fluorescence imaging with a wide optical range is important for clinical applications. In this work, a solution synthesis method was used for making Ag–Ho, Ag–Sm, Ag–Zn, Ag–Cu Ag–Cs, Ag–Zr, Ag–Er, Ag–Y and Ag–Co metal organic compound nanoparticles. XRD, XPS and TEM were carried out for sample characterization. They showed broad fluorescence from the UV to NIR region. In particular, they presented near-infrared (NIR) fluorescence (800–1100 nm) when excitation light of 785 nm was used. Furthermore, a white-to-green or blue-to-white transition was observed when excitation light varied from 290 nm to 370 nm. Proof-of-concept experiments were performed via UV light (359–371 nm), blue light (450–490 nm), green light (540–552 nm) and NIR light (center wavelength = 785 nm) excitation with pig-kidney tissue samples. They showed potential for biomedical fluorescence imaging in the UV-Vis-NIR range.